Job search methods, intensity and success in Britain in the 1990s - René Böheim; Mark P. Taylor (University of Essex, Institute for Social and Economic Research (ISER), 2001)
We investigate the use of various job search strategies and their impact on the probability of subsequent employment and the re-employment wage among working age men in Britain. We find that replying to advertisements and using Job Centres are the two most common methods of job search, and that job search intensity, and direct applications to employers in particular, result in a higher probability of subsequent employment. Conditional on finding work, replying to advertisements results in higher paying employment. Age, education, family circumstances and local labour demand, as well as unobserved individual specific effects, emerge as key determinants of job search strategy use and success
Keywords: 330